One-dimensional lead borate nanowhiskers for the joint shielding of neutron and gamma radiation: controlled synthesis, microstructure, and performance evaluation. Issue 48 (27th November 2017) - Wu, You; Zhang, Quan-Ping; Zhou, Dong; Liu, Li-Ping; Xu, Yun-Chuan; Xu, Dui-Gong; Zhou, Yuan-Lin
Abstract : The controlled synthesis of lead borate nanowhiskers and their highly effective co-shielding of neutron and gamma radiation was investigated. Abstract : Lead borate nanowhiskers have been successfully prepared by a facile solvothermal method. The morphologies and crystal sizes of the lead borate nanowhiskers are controlled by adjusting the amount of added ammonia hydroxide in the solvothermal reaction. The morphology evolution and structure changes are tracked during the growth process by field SEM, TEM, and XRD, respectively. The as-prepared lead borate nanowhiskers are 60–90 μm in length and 150–500 nm in diameter and possess typical single-crystal attributes. The influence of lead borate nanowhiskers on the mechanical properties, thermal conductivity, and radiation shielding performance of polymer composites is also discussed. The results show that lead borate nanowhiskers can significantly improve these properties of the composites. The excellent integrated properties contribute to the application of the materials for shielding mixed neutron and gamma radiation.